إنشاء ملصق تجاري لمعصرة زيت الزيتون بالبقاليش - الكوميتي, شيماء (مكتبة كلية الأدب العربي والفنون, 2023)
معاصر الزيتون لها دورا مهما في حياة الإجتماعية والاقتصادية، لما تعطينا من فوائد كثيرة سواء في ما يخص مجال التغذية، أم مجال الصحة...الخ، كما وجدنا بأن تنوع المصانع كان بتنوع جودة ونوعية منتوج زيت زيتون، أيضا توجد المصانع غير معروفة بسبب عدم تروجيها الجيد للمنتوج، في حين يوجد مصانع تحقق أرباح كثيرة بسبب تسوقيها للمنتوج، وتوفرها على تصاميم وملصقات تجدب المشتري، وتساعد على نشر المنتوج وبيعه لتحقيق أرباح كثيرة، أيضا قمنا في بحثنا بدراسة ميدانية على معصرة زيت الزيتون بالبقاليش، وصممنا ملصق تجاري له. Contemporary oil presses play an important role in social and economic life,offering us numerous benfits,whether in terms of nutrition,health,andmore.We’ve also observed that the diversity of factories is reflected in the quality and type of olive oil products.Some lesser-known factories have gone unnoticed due to poor product promotion,while others have achieved significant profits through effective marketing, appealing designs,and labels that attract buyers,thus facilitating the distribution and significant the distribution and sale of products to realize significant gains.Furthermore,We conducted a field study on the olive oil press in Al-bekkalish and created a commercial label for it.
Keywords: زيت الزيتون، معصرة بقاليش، التصميم، ملصق; Olive oil,al-bekkalish olive press, design,label.